2013
DOI: 10.2105/ajph.2013.301328
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Antiretroviral Treatment Among HIV-Infected Pregnant Medicaid Enrollees, 2005–2007

Abstract: Objectives We examined racial/ethnic differences in prenatal antiretroviral (ARV) treatment among 3259 HIV-infected pregnant Medicaid enrollees. Methods We analyzed 2005–2007 Medicaid claims data from 14 southern states, comparing rates of not receiving ARVs and suboptimal versus optimal ARV therapy. Results More than one third (37.3%) had zero claims for ARV drugs. Three quarters (73.4%) of 346 Hispanic women received no prenatal ARVs. After we adjusted for covariates, Hispanic women had 3.89 (95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As argued previously, this strategy can include many individuals without HIV disease, who did not seek (and did not need) HIV treatment. 12 Similarly, Zhang and coauthors 21 reported that 37.3% of HIV-positive Medicaid-enrolled pregnant women received no ARV treatment in pregnancy. As screening pregnant women for HIV is the standard of care, 22 this method may include many who were only screened for HIV, but did not have HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…As argued previously, this strategy can include many individuals without HIV disease, who did not seek (and did not need) HIV treatment. 12 Similarly, Zhang and coauthors 21 reported that 37.3% of HIV-positive Medicaid-enrolled pregnant women received no ARV treatment in pregnancy. As screening pregnant women for HIV is the standard of care, 22 this method may include many who were only screened for HIV, but did not have HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Persons from these states account for approximately one third of all US Medicaid enrollees and about half of all African American Medicaid enrollees in the United States. 39 These states, mostly in the southern United States, also account for the greatest burden of HIV among older people. 1 Medicaid is also the largest source of health coverage for PLWHA.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Unfortunately, health disparities in access to ART as well as the demands of long-term medication adherence have meant that the full benefits of HIV treatment are often not realized. (2 3) Adverse social conditions of poverty are among the most consistent predictors of disease progression and morbidity in people living with HIV. (4) Food insecurity, defined as limited access to nutritious food to meet dietary needs for an active and healthy life, is prevalent in US urban centers among people living with HIV.…”
mentioning
confidence: 99%